2017
DOI: 10.1590/1678-457x.14916
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the addition of peach palm (Bactris gasipaes) peel flour on the color and sensory properties of cakes

Abstract: This study aimed to evaluate the color and sensorial characteristics of a cake made with different amounts of flour made with peach palm peel flour. The flour was added at different concentrations, 2.5, 5.0, 7.5, and 10% (w/w), including a control (tartrazine). Physiochemical analyses were carried out on the cakes, including total carotenoids, CIE-L*a*b* color coordinates, and sensorial attributes. The results demonstrated that the peach palm peel flour substitution increased the total carotenoid content of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…It is important that the market offers bakery products containing the same sensory and nutritional quality as products that present gluten to people with celiac disease (Tracy, 1987). Martínez-Girón et al (2017) developed cakes with different proportions of peach palm flour, and the authors found in their studies that the peel flour can be considered as a natural food coloring alternative for cooked products, in order to replace artificial food coloring, besides increasing the biological properties of cakes.…”
Section: Physicochemical Compositionmentioning
confidence: 99%
“…It is important that the market offers bakery products containing the same sensory and nutritional quality as products that present gluten to people with celiac disease (Tracy, 1987). Martínez-Girón et al (2017) developed cakes with different proportions of peach palm flour, and the authors found in their studies that the peel flour can be considered as a natural food coloring alternative for cooked products, in order to replace artificial food coloring, besides increasing the biological properties of cakes.…”
Section: Physicochemical Compositionmentioning
confidence: 99%
“…This type of investigation may be carried out by moisture sorption isotherms, which provide key information to the development and optimization of food processes through the possibility of prediction of moisture adsorption and desorption data along storage at different relative humidity conditions ( Chisté et al., 2012 ; Carmo and Pena, 2019 ). There are available reports concerning the study of the technological potential of peach palm fruits to produce flour, from both their pulps ( Ferreira and Pena, 2003 ; Pires et al., 2019 ) or peels ( Órdóñez-Santos et al., 2016 ; Martínez-Girón et al., 2017 ). In addition, the hygroscopic behaviour of a flour prepared with oven-dried pulps of peach palm fruits was determined only by the acquisition of adsorption data at 15 °C and 35 °C ( Ferreira and Pena, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to that incorporation of RBP caused relatively dark color. The darkness increased with increasing the RBP% in biscuits, hence was reflected on L values (Table 4) which may be due to the non-enzymatic browning reactions (Martínez- Girón et al, 2017). A significant decrease p≤0.05) in the color scores were observed with increasing the RBP% in biscuits.…”
Section: Sensory Evaluation Results Of Biscuitsmentioning
confidence: 95%